Angle-dependent rotation velocity consistent with ADP release in bacterial F1-ATPase - Suiter, Nathan; Volkán-Kacsó, Sándor (Frontiers in Molecular Biosciences, 2023)
A model-based method is used to extract a short-lived state in the rotation kinetics of the F 1 -ATPase of a bacterial species, Paracoccus denitrificans (PdF1). Imaged as a single molecule, PdF1 takes large 120 ø steps during it rotation. The apparent lack of further substeps in the trajectories not only renders the rotation of PdF1 unlike that of other F-ATPases, but also hinders the establishment of its mechano-chemical kinetic scheme. We addressed these challenges using the angular velocity extracted from the single-molecule trajectories and compare it with its theoretically calculated counterpart. The theory-experiment comparison indicate the presence of a 20µs lifetime state, 40 o after ATP binding. We identify a kinetic cycle in which this state is a threenucleotide occupancy state prior to ADP release from another site. A similar state was also reported in our earlier study of the Thermophilic bacillus F 1 -ATPase (lifetime ∼ 10µs), suggesting thereby a common mechanism for removing a nucleotide release bottleneck in the rotary mechanism.